Restorative effects of Chrysin pretreatment on oxidant–antioxidant status, inflammatory cytokine production, and apoptotic and autophagic markers in acute paracetamol‐induced hepatotoxicity in rats: An experimental and biochemical study. Issue 11 (6th July 2017) - Eldutar, Eyup; Kandemir, Fatih Mehmet; Kucukler, Sefa; Caglayan, Cuneyt
Abstract: Paracetamol (PC) is a widely used analgesic and antipyretic drug, but it leads to acute hepatotoxicity at high doses intakes. This study was aimed to investigate the effects of Chrysin (CR) on hepatotoxicity constituted at high doses of PC in rats. Rats were subjected to oral pretreatment of CR (25 and 50 mg/kg b.w.) via feeding needle for 6 days against hepatotoxicity induced by a single dose of PC (500 mg/kg b.w.) administered orally via feeding needles. Although PC increases lipid peroxidation and liver enzyme activities, it has led to reduction of antioxidant enzyme activities. PC induced inflammatory responses by increasing the levels of TNF‐α and IL‐1β. Furthermore, PC caused apoptosis and autophagy by increasing activity of Caspase‐3 and LC3B level. On the other hand, CR therapy significantly regulated these values in rats. This study demonstrated that CR possesses restorative effect against PC‐induced hepatotoxicity by suppressing oxidative stress, inflammation, and apoptotic and autophagic tissue damage.